Strategi Komisi Penanggualangan AIDS (KPA) Dalam Melakukan Pencegahan Penularan Pada Remaja Di Kota Cirebon - Nabila, Mau’idzotun Nisa’an; Sriyani, Tini; Mubarok, Muhammad Adib; Istiqomah, Istiqomah (Institut Agama Islam Negeri (IAIN) Kudus, 2025)
The AIDS Commission (KPA) Strategy in Preventing Transmission Among Adolescents in Cirebon City. HIV (Human Immunodeficiency Virus) and AIDS (Acquired Immunodeficiency Syndrome) are two health issues that have attracted global attention for several decades. Despite the significant advancements made in HIV therapy and treatment, prevention still plays a crucial role in efforts to control the virus's causes and mitigate the consequences for individuals and society. This research aims to understand the strategies used by the AIDS Prevention Commission in preventing transmission among adolescents in Cirebon City, with a focus on prevention aspects. Although the AIDS Prevention Commission (KPA) has been doing well and operating in accordance with its duties to prevent HIV/AIDS in Cirebon City, not only focusing on adolescents but also on the community in Cirebon City. The activities that are specifically focused on adolescents include the Youth Health Post (Posyandu Remaja). This activity focuses on providing education and understanding about the importance of HIV/AIDS prevention as well as materials related to youth issues. In addition, there is a primary hindering factor faced, which is the lack of understanding among adolescents about HIV/AIDS, making it difficult to conduct screenings, and this will become a problem that needs to be addressed immediately. This will affect the ongoing activities of HIV/AIDS prevention. This research is descriptive qualitative with data collection through interviews, observations, and documentation, involving KPA institutions and other related actors. Data analysis is conducted through data mining, data reduction, and conclusion drawing, using source triangulation. The results of the study show that, despite the occurrence of several inhibiting factors. This research recommends direct intervention from stakeholders to assist adolescents who do not yet understand the knowledge related to HIV/AIDS.